Gun violence - Steffens, Bradley, 1955- (Emerging issues in public health., 2020)
Examines the dangers surrounding gun violence and discusses how it has become a rising public health crisis. Explores what is being done to curb gun violence and prevent suicide. Includes quotes, sidebars, color photographs, and further resources.